IL10 promoter rs6667202 polymorphism is functional in health but not in grade c periodontitis patients: A pilot study - Stolf, Camila S.; Sacramento, Catharina M.; Paz, Hélvis E. S.; Machado, Renato A.; Ramos, Lucas P. [UNESP]; de Oliveira, Luciane D. [UNESP]; Cogo-Müller, Karina; Santamaria, Mauro P. [UNESP]; Ruiz, Karina G. S.; Casarin, Renato C. V. (Wiley, 2022)
Background and objective: Previous studies have demonstrated an association between the IL10 promoter rs6667202 (C > A) single-nucleotide polymorphism (SNP) and grade C, stage 3 or 4 periodontitis (Perio4C) in the Brazilian population, where the altered A allele was detected more frequently in these patients. However, no functional analysis of this variation has yet been performed. Thus, the objective of this preliminary study was to evaluate the functionality of rs6667202 in gingival fibroblasts (GFs) of individuals with Perio4C and with periodontal health (PH) stimulated with Aggregatibacter actinomycetencomitans protein extract (AaPE). Methods: Patients with PH and Perio4C were segregated according to their genotype (AA, AC, or CC), and a biopsy was performed to establish the culture of the GFs. After GFs exposure to AaPE at 5 µg/ml for 1.5 h, RNA was extracted to analyze IL10 expression by qPCR. Aliquots of the cell's supernatant were subjected to immunoenzymatic analysis (MAGpix) to detect interleukin-10 (IL-10). Results: In PH, the genotypes AA and AC are related to less expression of IL10 (p = 0.027 and p < 0.0001) and less production of IL-10 (p = 0.002 and p = 0.001), when compared to CC. In Perio4C, there was no statistical difference between the genotypes (p > 0.05), although a lower IL-10 expression and release compared with PH CC was seen (p = 0.033 and p < 0.001). Conclusion: The rs6667202 SNP is functional in PH, as it decreases the expression and production of IL-10. In Perio4C, other factors may be masking its action by altering the IL-10's response.